Recent research progress on metal ions and metal-based nanomaterials in tumor therapy - Xu, Yongcheng; Reheman, Aikebaier; Feng, Wenhua (Frontiers in Bioengineering and Biotechnology, 2025)
Tumors, as a disease that seriously threatens human health, have always been a major challenge in the field of medicine. Currently, the main methods of tumor treatment include surgery, radiotherapy, chemotherapy, etc., but these traditional treatment methods often have certain limitations. In addition, tumor recurrence and metastasis are also difficult problems faced in clinical treatment. In this context, the importance of metal-based nanomaterials in tumor therapy is increasingly highlighted. Metal-based nanomaterials possess unique physical, chemical, and biological properties, providing new ideas and methods for tumor treatment. Metal-based nanomaterials can achieve targeted therapy for tumors through various mechanisms, reducing damage to normal tissues; they can also serve as drug carriers, improving the stability and bioavailability of drugs; at the same time, some metal-based nanomaterials also have photothermal, photodynamic, and other characteristics, which can be used for phototherapy of tumors. This review examines the latest advances in the application of metal-based nanomaterials in tumor therapy within past 5 years, and presents prospective insights into the future applications.